2015
DOI: 10.1002/chem.201501304
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Total Synthesis of Bongkrekic Acid and Apoptosis Inhibitory Activity of Its Analogues

Abstract: Bongkrekic acid (BKA), isolated from the bacterium Burkholderia cocovenenans, is an inhibitor of adenine nucleotide translocator, which inhibits apoptosis, and is thus an important tool for the mechanistic investigation of apoptosis. An efficient total synthesis of BKA has been achieved by employing a three-component convergent strategy based on Kocienski-Julia olefination and Suzuki-Miyaura coupling. It is noteworthy that segment B has been prepared as a new doubly functionalized coupling partner, which contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…We recently established a total synthesis method for BKA with high purity (>98%). 19) We also reported that chemically synthesized BKA promoted PPARγ transcriptional activity in MCF-7 breast cancer cells. 20) We herein investigated whether BKA, together with its analogs newly synthesized in this study ( Fig.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…We recently established a total synthesis method for BKA with high purity (>98%). 19) We also reported that chemically synthesized BKA promoted PPARγ transcriptional activity in MCF-7 breast cancer cells. 20) We herein investigated whether BKA, together with its analogs newly synthesized in this study ( Fig.…”
mentioning
confidence: 78%
“…1) were synthesized using established methods. 19,21) The purities of these compounds were found to be >98% by HPLC or column chromatography. PIO and dexamethazone (DEX) were purchased from Wako Pure Chemical Industries, Ltd. (Osaka, Japan) (purity: 98%, HPLC).…”
Section: Methodsmentioning
confidence: 98%
“…BKA and BKA derivatives (BKA-2 and BKA-3) were synthesized according to established methods (18,19). BKA-1' and BKA-4 were newly synthesized according to previously described methods (18,19). The purities of these compounds were found to be >98% by high-performance liquid chromatography (HPLC) and column chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…BKA may be obtained from commercial sources; however, its purity is generally low (approximately 90-95%). We originally established synthetic methods for BKA with high purity (>98%) (18). In the present study, we investigated whether BKA negatively affects the viability of LTED cells by comparing its effects on other breast cancer cell lines, namely, MCF-7 cells (i.e., the parental cells of LTED cells) and MDA-MB-231 cells.…”
mentioning
confidence: 99%
“…Removal of the highly acidic proton on C23 in 405 may result in an allene or alkyne. On the other hand, coupling with 404 as segment of A successfully gave the desired product 405 , containing entire BKA scaffold, in excellent yield (Scheme ) …”
Section: Coupling Of Sp2 Hybridized C–b Compoundsmentioning
confidence: 99%